Evaluasi Peranan Persepsi Kegunaan dan Sikap Terhadap Penerimaan Sistem Informasi Manajemen Rumah Sakit (SIMRS) di Rumah Sakit Daerah Kalisat - Seila Riska Faricha Daerina; Yusi Tyroni Mursityo; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The large amount of investment for the implementation of Hospital Management Information System (SIMRS) in Rumah Sakit Daerah Kalisat, become the main reason to evaluate the implementation of the system that has been running. In order to support service performance, all employees as SIMRS users are expected to have a full commitment on using SIMRS, so it is necessary to identify the factors that influence user acceptance. This study was conducted to evaluate SIMRS acceptance by measuring the perception of the employee's usefulness towards SIMRS and see how its effect on employee's intention to use SIMRS. As well as measure the attitude of employees as an acceptance or rejection feeling towards SIMRS and how its effect on employee's intention to use SIMRS. This study also conducted a test to find mediation effect by attitudes. From the whole population, 56 employees randomly selected as samples and was stratified according to their jobs. The result of hypothesis testing by using Partial Least Square, showed that there is no positive and significant effect from perceived usefulness towards behavioral intention, there was a positive and significant effect from attitudes towards behavioral intention and there can't be found the mediating effect by attitude. The results of the evaluation supported by observation and interview that the current implementation of SIMRS has not been able to support a full medical records and reporting process, and employees should be given the opportunity to use SIMRS consistently, in order to build their positive attitude towards SIMRS.